An ecological study into the possible reclamation value of reedbeds in a coal mine wetland system in Kwazulu-Natal / Michelle Boshoff - Boshoff, Michelle (North-West University, 2009)
The single biggest environmental problem facing the coalmine industry today is the high acid concentration in mine runoff water. After pollution prevention and effluent reuse, reclamation is the most important component of a mine management strategy. Major interest has developed in the concept of constructed wetlands for the treatment of point source pollution. Research, both internationally and national, indicates that reed-bed systems can provide effective and adaptable water purification systems. Inside this intricate aquatic ecosystem, organisms fulfil an important role in the energy dynamics of wetlands. Organisms can be used as bio-indicators to determine the system performance and yield important information and data that will attribute to our knowledge of wetlands. The aim of this study was to develop a biological and chemical database (BCD) for a constructed coal-mine wetland in Natal. The study was conducted at the Sithebe wetland at Hlobane Mine, 25 km east of Vryheid, in KwaZulu-Natal. Data (physio-chemical and biological) were collected on a monthly basis from March 1998 to February 1999. This study incorporated the physical, chemical, and biologic aspects of the wetland into an integrated measure of wetland health. It also emphasise the need to reduce large data sets for particular areas to a single value (acceptable or unacceptable, in terms of the environmental condition). In terms of providing biological input, this project on the flora and fauna of the Sithebe wetland could prove to be useful in its contribution to measurements of degradation/improvement, as well as providing a comprehensive picture of the structure and fluctuation of the communities of a constructed wetland. The results of the study have indicated that the constructed Sithebe wetland system functioned as a complex and diverse ecosystem. Even though Phragmites australis was the dominant plant species in the wetland, various other species (six other plant communities) established themselves in the wetland. The heterogeneous composition of the artificial wetland contributed to reduction in element loads and various species seemed to assist in the removal of different elements like magnesium, iron, manganese, zinc, selenium and lead. The continued development of scientific knowledge and expertise in South Africa is fundamental to the achievement of wetland conservation. This research project was aimed at promoting the management of wetlands that is based on a predictive understanding of the ecology and behaviour of these systems and their components. === Thesis (M.Sc.)--North-West University, Potchefstroom Campus, 2005.